TNF-α Downregulation Modifies Insulin Receptor Substrate 1 (IRS-1) in Metabolic Signaling of Diabetic Insulin-Resistant Hepatocytes - Iraj Alipourfard; Nelly Datukishvili; Davit Mikeladze (Hindawi Limited, 2019)
One of the major mechanisms of hyperglycemia in type 2 diabetes is insulin resistance (IR) which can induce free fatty acids like palmitate. In hepatic cell, as an insulin target tissue, insulin resistance can be stimulated by inflammatory cytokine TNF-α. The interaction of intracellular TNF-α signal with the insulin signaling pathway is not well identified. Hence, we aimed to investigate the effect of TNF-α elimination on the diabetic model of palmitate-induced insulin-resistant hepatocytes (HepG2). The changes of phosphorylation rate in IRS-1 protein are determined to know the effect of TNF-α on this key protein of the insulin signaling pathway. HepG2 cells were treated with 0.5 Mm palmitate, and TNF-α gene knockdown was performed by shRNA-mediated technique. Western blot analysis was used to evaluate the phosphorylated activity of the insulin signaling pathway. Palmitate-induced IR could increase TNF-α protein expression 1.2-, 2.78-, and 2.25-fold compared to the control cells at times of 8 h, 16 h, and 24 h, respectively. TNF-α expression in downregulated cells transfected with shRNA-TNF-α is approximately 47.0% of normal cells and 49.0% in the case of scrambled cells. IRS-1 phosphorylation in TNF-α-downregulated and stimulated cells with 100 nM insulin, after treatment and in the absence of palmitate, was 45% and 29% higher than the normal cells. These data support the evidence that TNF-α downregulation strategy contributes to the improvement of IRS-1 phosphorylation after insulin stimulation and insulin response in HepG2 liver cells.